Dinamika Sosial, Ekonomi, dan Lingkungan dalam Pembentukan Permukiman Kumuh di Tepi Sungai - Yuda, Nur Ad'ha (Nusantara Journal of Science and Technology, 2025)
The rapid increase in population and urbanization in developing countries has led to the proliferation of slum settlements, particularly in riverfront areas. This study examines the factors influencing the formation of slum settlements on or near rivers, focusing on the socio-economic and environmental impacts and the efforts to address these challenges. Indonesia, with its numerous rivers, provides a critical case study. The traditional practice of living by the rivers for essential needs like water and transport has evolved into densely populated slum areas due to insufficient government regulation and economic constraints. These settlements face significant challenges, including inadequate infrastructure, poor sanitation, high flood risk, and environmental degradation. The study employs a literature review method, analyzing various academic journals, research reports, and government policies to understand the dynamics of riverfront slums. It also includes case studies from Makassar, Palembang, and Banjarmasin in Indonesia, highlighting the socio-economic conditions, physical characteristics, and environmental issues of these slums. The findings emphasize the need for integrated approaches involving infrastructure improvement, strict regulations, community education, and participatory planning to enhance living conditions and sustainability in riverfront slum settlements. Recommendations are provided for evidence-based policies and interventions to effectively tackle the complex issues associated with slum settlements on or near rivers.